Achondrogenesis type II with normally developed extremities: a case report - Kocakoc, E; Kiris, A (John Wiley & Sons Ltd, 2002)
We present a case of achondrogenesis type II with normally developed extremities that was confirmed with postmortem ultrasonographic and radiographic examination. The length of the long bones may vary and the diagnosis of achondrogenesis should not be ruled out With normally developed extremities. Intrauterine sonographic examination of the vertebrae is very important and the absence of vertebral body ossification may be the unique finding of achondrogenesis type II. Axial Ultrasonographic images and postmortem plain radiographs are useful to clarify the pathology. Copyright (C) 2002 John Wiley Sons, Ltd.
Keywords: achondrogenesis type II; ultrasonography; normal extremity